2009
DOI: 10.1089/jir.2008.0076
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Augments TNF-α–Mediated Inflammatory Responses from Lung Epithelial Cells

Abstract: Interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) mediate the development of numerous inflammatory lung diseases. Since IL-1β is typically activated in situations where TNF-α is produced, it was hypothesized that IL-1β alters TNF-α-induced proinflammatory epithelial cell function by altering TNF receptor shedding and surface abundance. In this study, the impact of IL-1β on TNF-α-mediated chemokine production as well as TNF receptor surface expression and shedding were investigated from mouse pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 52 publications
4
69
0
1
Order By: Relevance
“…Cell apoptosis is evoked by multiple pathways but mainly the intrinsic and extrinsic signaling cascades, both of which result in activation of executor caspases through the initiator caspase Cas-8 [51]. The association of TNF-α with TNFR [12] on the cell surface recruits TRADD, FADD to form the cytosolic platform of DISC as a ligand-dependent transmembrane signaling receptor [52] that initiates inflammation [16] and apoptosis cascade [17,18]. DISC provokes the Cas-8 to activate Cas-3, which sabotages a range of cytoplasmic proteins and dismantles chromatin and nucleoplasmic proteins in the nucleus, eventually resulting in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis is evoked by multiple pathways but mainly the intrinsic and extrinsic signaling cascades, both of which result in activation of executor caspases through the initiator caspase Cas-8 [51]. The association of TNF-α with TNFR [12] on the cell surface recruits TRADD, FADD to form the cytosolic platform of DISC as a ligand-dependent transmembrane signaling receptor [52] that initiates inflammation [16] and apoptosis cascade [17,18]. DISC provokes the Cas-8 to activate Cas-3, which sabotages a range of cytoplasmic proteins and dismantles chromatin and nucleoplasmic proteins in the nucleus, eventually resulting in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that IL-1b could be upstream of TNF-a and TNFR. Most importantly, IL-1b secretion is negatively regulated by NF-kB activity (7,25). During the initial phase of GVHD, pro-IL-1b production is promoted, whereas its processing and secretion are inhibited by the activation of NF-kB through the inhibition of caspase-1 by NF-kB-dependent gene products.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that IL-1b could modulate TNF-a-mediated inflammatory lung diseases (24). Moreover, IL-1b secretion was negatively regulated by NF-kB activity (7,25). Therefore, IL-1b could be the cytokine affected directly by delayed bortezomib administration.…”
Section: Il-1b Blockade Protects Mice From Lethal Gvhd Caused By Delamentioning
confidence: 99%
“…Furthermore, production of IFN-␥ by SCID mouse splenocytes stimulated with IL-12 plus TNF was completely ablated by administering anti-IL-1␤ (69). As a pleotropic mediator of inflammation, IL-1␤ mediates its protective effects via multiple mechanisms, including enhancing expression of the TNF receptor, which may explain the synergistic effect of IL-1␤ and TNF (70). While TNF alone is unable to significantly increase the antiparasitic activity of macrophages, TNF synergizes with IFN-␥ to enhance it (68).…”
Section: Il-12 Production Is Essential For Ifn-␥ Production By Nk mentioning
confidence: 99%